2001
DOI: 10.1006/jcec.2000.1703
|View full text |Cite
|
Sign up to set email alerts
|

Corruption and Economic Growth

Abstract: Mo, Pak Hung-Corruption and Economic GrowthThis study introduces a new perspective on the role of corruption in economic growth and provides quantitative estimates of the impact of corruption on the growth and importance of the transmission channels. In our ordinary least squares estimations, we find that a 1% increase in the corruption level reduces the growth rate by about 0.72% or, expressed differently, a one-unit increase in the corruption index reduces the growth rate by 0.545 percentage points. The most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
603
7
57

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,020 publications
(705 citation statements)
references
References 16 publications
38
603
7
57
Order By: Relevance
“…Similarly, when adding the structural reform index to the growth regression which includes a corruption index, initial real per capita GDP, initial life expectancy, inflation rate and the ratio of fiscal balance to GDP, the coefficient on corruption index also became insignificant (Abed & Davoodi, 2000 [29]). Other authors such as Mo (2001) [30], and Pellegrini and Gerlagh (2004) [20] also confirmed this finding. This trend could be interpreted that the effect of corruption on economic growth is transmitted through other determinants of growth (Dridi, 2013) [24].…”
Section: Review Of Empirical Studiessupporting
confidence: 73%
See 3 more Smart Citations
“…Similarly, when adding the structural reform index to the growth regression which includes a corruption index, initial real per capita GDP, initial life expectancy, inflation rate and the ratio of fiscal balance to GDP, the coefficient on corruption index also became insignificant (Abed & Davoodi, 2000 [29]). Other authors such as Mo (2001) [30], and Pellegrini and Gerlagh (2004) [20] also confirmed this finding. This trend could be interpreted that the effect of corruption on economic growth is transmitted through other determinants of growth (Dridi, 2013) [24].…”
Section: Review Of Empirical Studiessupporting
confidence: 73%
“…Mauro (1995) [18] employed cross-section data including 58 countries during the 1960−85 period and found that the negative relationship between corruption and economic growth is statistically and economically significant. The negative relationship between corruption and growth was later confirmed by many empirical studies [Mauro (1997) [18], Tanzi (1998) [14], Mo (2001) [19], Pellegrini & Gerlagh (2004) [20], Pierre-Guillaume & Khalid (2005) [21], [22 & Herzfeld (2005) [22], Hodge et al (2009) [23], and Dridi (2013) [24]]. Besides data issues, these empirical studies question the causality and the robustness of the relationship between economic growth and corruption, as we now explain.…”
Section: Review Of Empirical Studiesmentioning
confidence: 81%
See 2 more Smart Citations
“…On distingue pour cela les effets directs et indirects de la corruption en utilisant une méthode d'analyse basée sur celle de Mo (2001).…”
Section: La Mise En éVidence Des Principaux Canaux De Transmissionunclassified